SIMPLE BIOMARKER ANALYSIS OF SYSTEMIC INFLAMMATION IN AGITATION AMONG SCHIZOPHRENIA PATIENTS: CROSS-SECTIONAL STUDY - Ratnawati, Tri; Kartikasari, Linda; Sarjana, Widodo (Departemen Psikiatri Fakultas Kedokteran Universitas Brawijaya, 2025)
Introduction: Schizophrenia is a serious mental disorder characterized by reality distortion and psychomotor disorganization, with agitation as a common symptom that increases the risk of rehospitalization. Systemic inflammation, measured by biomarkers such as the neutrophil-to-lymphocyte ratio (NLR), monocyte-to-lymphocyte ratio (MLR), platelet-to-lymphocyte ratio (PLR), and systemic immune-inflammation index (SII), has been identified as being associated with the pathophysiology of schizophrenia. This study aims to investigate the relationship between agitation and inflammation, as indicated by elevated NLR, MLR, PLR, and SII values, in schizophrenia patients. Methods: A retrospective cross-sectional study was conducted involving 314 schizophrenia patients hospitalized at Dr. Amino Gondohutomo Mental Hospital, Semarang, from December 2023 to July 2024. Data was collected from medical records, including NLR, MLR, PLR, and SII values calculated from routine hematological exams, and the degree of agitation measured with the PANSS-EC scale. Results: The majority of patients (65.3%) were aged 18-37 years, with a mean age of 34.07 years. Most patients were male (52.5%) and exhibited moderate agitation (66.6%). Regression analysis showed that NLR, MLR, and SII values were significantly positively correlated with agitation levels. NLR had a regression coefficient of 0.122 (p=0.001), MLR of 0.293 (p=0.046), and SII of 0.000 (p=0.035), indicating that increases in these inflammatory biomarkers correlated with higher agitation levels in schizophrenia patients. Discuss: Hematological biomarkers such as Neutrophil-to-Lymphocyte Ratio (NLR), Monocyte-to-Lymphocyte Ratio (MLR), and Systemic Immune-Inflammation Index (SII) hold significant potential in psychiatric emergency settings as simple, cost-effective, and accessible tools for early identification and risk stratification of acute agitation in schizophrenia and other severe mental disorders. Conclusion: This study found that elevated NLR, MLR, and SII values were closely associated with increased agitation levels in schizophrenia patients, supporting the hypothesis that systemic inflammation plays a role in the pathophysiology of schizophrenia. These findings suggest the potential for using inflammatory biomarkers as predictive tools for assessing agitation severity in schizophrenia patients, which could aid in clinical management and rehospitalization prevention.